RECVOICE: uma plataforma digital para acervo, pesquisa e seleção de vozes de profissionais do Recife. - Santana, Glaucenira Neves Correia (2024)
This technical report is about RECVOICE a digital platform for collection, research and selection of voices aimed at voice actors from Recife with professional interests in entering, mainly, in the national dubbing, original voice and game localization market, remotely, a real possibility that arose with the COVID-19 health crisis. Based on practices that have already been applied in Recife on an individual basis by these voice professionals, the tool is under construction and presents itself as something capable of giving greater and better visibility to this category, facilitating its direct connection with studios, clients and producers local and national audio and video companies, who are looking for the ideal voice for their projects. It works as a contact network, where you can find profiles of professionals, their vocal skills and work samples. The product is supported by exploratory research associated with qualitative research through focus groups.